Theories of Economic Fluctuations and their Influence on the Formation of the Modern Paradigm of Economic Activity of Enterprises - Kashchena, N. (Економічний вісник Донбасу, 2020)
The article is devoted to the substantiation of the influence of the theory of economic fluctuations on the economic activity of enterprises. The influence of economic fluctuations at the macrolevel of the economy on economic activity at the microlevel of business entities is noted. A systematic approach to determining the economic activity of the enterprise as a phenomenon with a complex internal structure is analyzed in detail. Peculiarities of determining the effect of systematization in the interaction of components of business activity of the enterprise are analyzed: economic, managerial, financial, innovative, investment, marketing, labor, production. Attention is focused on the main goal in the management of the business activity of the enterprise as the formation of all types of activity at the exit from the system – it can be achieved by purposefully ensuring the activity of the enterprise both at the entrance to the system and in the process of transformation. The phases of formation of economic activity of the enterprise according to the theory of economic fluctuations are separated: formation; growth; maximum value; reduction. It is proved that at each phase of the business cycle the economic behavior of the enterprise changes. The urgency of measures to assess economic activity in the system of assessing the overall business activity of economic entities has been stated. The internal and external factors influencing the change of economic activity of the enterprise are defined. The importance of assessing the activity of the enterprise in the management system of economic activity as a system of "entrance-exit" of the relevant indicators is considered. The formation of control and managed subsystems in the mechanism of management of economic activity of enterprises in market conditions is analyzed. The main result of the study is the development of a management system of economic activity as a component of business activity of enterprises. Effective recommendations to ensure a high level of economic activity of enterprises in an unstable market environment are provided. Стаття присвячена обґрунтуванню впливу теорії економічних коливань на господарську діяльність підприємств. Визначено вплив економічних коливань на макрорівні економіки – на економічну активність, на мікрорівні – господарюючих суб'єктів. Детально аналізується системний підхід до визначення економічної діяльності підприємства як організації зі складною внутрішньою структурою. Аналізуються особливості визначення ефекту систематизації у взаємодії компонентів господарської діяльності підприємства: економічної, управлінської, фінансової, інноваційної, інвестиційної, маркетингової, трудової, виробничої. Увага акцентується на головній меті в управлінні господарською діяльністю підприємства як формуванні всіх видів діяльності на виході з системи – вона може бути досягнута шляхом цілеспрямованого забезпечення діяльності підприємства як на вході в систему, так і в процесі трансформації. Відповідно до теорії економічних коливань виділяються фази формування економічної діяльності підприємства: формування; зростання; максимальне значення; зниження. Доведено, що на кожній фазі ділового циклу змінюється економічна поведінка підприємства. Обґрунтовано актуальність заходів з оцінки економічної активності в системі оцінки загальної ділової активності господарюючих суб'єктів. Визначено внутрішні та зовнішні фактори, що впливають на зміну господарської діяльності підприємства. Розглянуто важливість оцінки діяльності підприємства в системі управління господарською діяльністю як системи "Вхід-Вихід" відповідних показників. Аналізується формування керуючої та керованої підсистем у механізмі управління господарською діяльністю підприємств у ринкових умовах. Основним результатом дослідження є розробка системи управління господарською діяльністю як складової підприємницької діяльності підприємств. Надано ефективні рекомендації щодо забезпечення високого рівня економічної активності підприємств в умовах нестабільного ринкового середовища. Статья посвящена обоснованию влияния теории экономических колебаний на хозяйственную деятельность предприятий. Отмечено влияние экономических колебаний на макроуровне экономики – на экономическую активность, на микроуровне – хозяйствующих субъектов. Подробно анализируется системный подход к определению экономической деятельности предприятия как явления со сложной внутренней структурой. Анализируются особенности определения эффекта систематизации во взаимодействии компонентов хозяйственной деятельности предприятия: экономической, управленческой, финансовой, инновационной, инвестиционной, маркетинговой, трудовой, производственной. Внимание акцентируется на главной цели в управлении хозяйственной деятельностью предприятия как формировании всех видов деятельности на выходе из системы – она может быть достигнута путем целенаправленного обеспечения деятельности предприятия как на входе в систему, так и в процессе трансформации. В соответствии с теорией экономических колебаний выделяются фазы формирования экономической деятельности предприятия: формирование; рост; максимальное значение; снижение. Доказано, что на каждой фазе делового цикла изменяется экономическое поведение предприятия. Обоснована актуальность мероприятий по оценке экономической активности в системе оценки общей деловой активности хозяйствующих субъектов. Определены внутренние и внешние факторы, влияющие на изменение хозяйственной деятельности предприятия. Рассмотрена важность оценки деятельности предприятия в системе управления хозяйственной деятельностью как системы "Вход-Выход" соответствующих показателей. Анализируется формирование управляющей и управляемой подсистем в механизме управления хозяйственной деятельностью предприятий в рыночных условиях. Основным результатом исследования является разработка системы управления хозяйственной деятельностью как составляющей предпринимательской деятельности предприятий. Даны эффективные рекомендации по обеспечению высокого уровня экономической активности предприятий в условиях нестабильной рыночной среды.